2012
DOI: 10.1017/s0022381612000394
|View full text |Cite
|
Sign up to set email alerts
|

Candidates Matter: Policy and Quality Differences in Congressional Elections

Abstract: We reexamine voting choice in congressional elections by using panels of district experts to identify the ideological positions and leadership qualities of candidates running in a national sample of districts. We show that: (1) candidate-quality differences affect voting choice; (2) that the effect of candidate quality increases with reduced differences between candidates on ideology; and (3) that the effect of issues on voting depends on candidate differences in quality and ideology. The conditional nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 55 publications
5
63
1
1
Order By: Relevance
“…We argue that ideological divergence exerts a weaker relationship on affective evaluations when the candidates' biographical characteristics are emphasized. This expectation is consistent with recent work on U.S. and European elections that studies the conditional relationships between candidate characteristics and ideology (Buttice and Stone 2012;Clark and Leiter 2014). When citizens receive information exclusively about the ideological differences between candidates or parties, this information dominates citizens' evaluative calculus; but when citizens are also presented with information about, for instance, the candidates' backgrounds, political experiences, and social group memberships, citizens incorporate this information into their evaluations and thus the effect of ideological differences attenuates.…”
Section: Ideological Differences Candidate Characteristics and Affesupporting
confidence: 90%
See 1 more Smart Citation
“…We argue that ideological divergence exerts a weaker relationship on affective evaluations when the candidates' biographical characteristics are emphasized. This expectation is consistent with recent work on U.S. and European elections that studies the conditional relationships between candidate characteristics and ideology (Buttice and Stone 2012;Clark and Leiter 2014). When citizens receive information exclusively about the ideological differences between candidates or parties, this information dominates citizens' evaluative calculus; but when citizens are also presented with information about, for instance, the candidates' backgrounds, political experiences, and social group memberships, citizens incorporate this information into their evaluations and thus the effect of ideological differences attenuates.…”
Section: Ideological Differences Candidate Characteristics and Affesupporting
confidence: 90%
“…As responsible party theorists (APSA Committee on Political Parties 1950) and spatial models of electoral competition (Downs 1957) have long argued, the consequences of electoral outcomes increase as the parties or candidates endorse increasingly distinct programs. Consistent with this expectation, more recent research finds that an increase in the ideological differences between candidates strengthens the connection between ideology and vote choice (Buttice and Stone 2012;Wright and Berkman 1986). Abramowitz (2010) similarly shows that increased party polarization in Congress has increased voter turnout by increasing the stakes associated with partisan control.…”
Section: Ideological Differences and Affective Polarizationmentioning
confidence: 91%
“…These results appear to indicate positive complementarity, in line with the findings of J. Green and Hobolt (2008) and Buttice and Stone (2012). On the spending dimension, since respondents hold a moderate position, this dynamics does not emerge as clearly.…”
Section: Figure 2 Competency Form: the Interaction Between Education supporting
confidence: 80%
“…We found that participants looked through the candidate posts, non-candidate posts, replies and images and evaluated them on three main criteria: issue, personality, and community related information. The findings on issue and personality were consistent with other studies that have also found these to be the main criterion of the vote decision [7,11,22]. We report here on the use of community as a voting criterion.…”
Section: Candidate Evaluation Using Facebooksupporting
confidence: 92%